Design of Searching System of Room Doctor and Patient Data at Hospital Based on Web Using Multi DBMS - Rima Maulini (Jurnal Ilmiah ESAI, 2011)
Information at a hospital is needed by patients or visitor. System bases on this web built to facilitate seeking of information about a patient taken care in certain hospital and room. Data of a patient would having drug to certain doctor, this application providesÂ  list of practicing doctor at certain hospital. System is designed by using three DBMS representing three hospitals. System who has three different databases can be integrated in one web application, so that user is not necessary to open many web applications for the same purpose.Â Key words: search engine, Multi DBMS, database